Helicobacter pylori-negative gastric mucosa-associated lymphoid tissue lymphomas: A review - Asano, Naoki (World J Gastroenterol, 2015)
Since Isaacson and Wright first reported on the extra-nodal marginal zone B-cell lymphoma of the stomach in 1983, following studies have clarified many aspects of this disease. We now know that the stomach is the most affected organ by this disease, and approximately 90% of gastric mucosa-associated lymphoid tissue (MALT) lymphomas are related to Helicobacter pylori (H. pylori) infection. This implies that approximately 10% of gastric MALT lymphomas occur independent of H. pylori infection. The pathogenesis of these H. pylori-negative gastric MALT lymphomas remains unclear. To date, there have been several speculations. One possibility is that genetic alterations result in nuclear factor-kappa B (NF-κB) activation. Among these alterations, t(11;18)(q21;q21) is more frequently observed in H. pylori-negative gastric MALT lymphomas, and such translocation results in the synthesis of fusion protein API2-MALT1, which causes canonical and noncanonical NF-κB activation. Another possibility is infection with bacteria other than H. pylori. This could explain why H. pylori eradication therapy can cure some proportions of H. pylori-negative gastric MALT lymphoma patients, although the bacteria responsible for MALT lymphomagenesis are yet to be defined. Recent advances in endoscopy suggest magnifying endoscopy with narrow band imaging as a useful tool for both detecting gastric MALT lymphoma lesions and judging the response to treatment. A certain proportion of H. pylori-negative gastric MALT lymphoma patients respond to eradication therapy; hence, H. pylori eradication therapy could be considered as a first-line treatment for gastric MALT lymphomas regardless of their H. pylori infection status.